Implementasi Program Roots dalam Pembentukan Akhlak Kepada Sesama di SMP PGII 2 Kota Bandung - Ridwan Ramli; Surbiantori, Eko; Rachmah, Huriah (UNISBA Press, 2024)
Abstract. The aim of moral formation is to make students become Muslims who have the quality of faith in the Creator, so that it can be applied in social life. Through this Roots Day program, students are taught good morals or attitudes in communicating with friends, in order to create a harmonious classroom sauna. Roots Day is a science-based program that aims to prevent bullying in schools by involving students as agents of change who create a positive atmosphere at school. This research aims to describe (1) to find out the implementation of Roots Day in forming morals towards others, (2) To find out the strategy of the Roots Day program in forming morals towards others, (3) To find out what the inhibiting and supporting factors are in the Roots Day Program in forming morals towards others. The results of the research show that: (1) The Roots Day program is implemented with theatrical performances regarding the dangers of bullying and anti-bullying declarations as a form of creating an anti-bullying zone in schools, (2) The strategy in implementing the Roots Day program is to shape student morals by providing explanations about the dangers. bullying, providing moral education, (3) Supporting factors include providing facilities and budget for Roots Day activities, students' enthusiasm in participating in Roots Day activities and enthusiasm of teachers and school residents in implementing Roots Day. Inhibiting factors include, some teachers have not received special training regarding agents of change in the Roots Day program, bad habits in the home environment that are carried over to school and differences in student characteristics. Abstrak. Tujuan dari pembentukan akhlak adalah untuk membuat siswa menjadi muslim yang memiliki kualitas keimanan kepada pencipta, sehingga dapat di aplikasikan dalam kehidupan sosial. Melalui program Roots Day ini siswa diajarkan akhlak atau sikap yang baik dalam berkomunikasi dengan teman, agar tercipta sauna kelas yang harmonis. Roots day merupakan program berbasis sains yang bertujuan untuk mencegah perundungan di sekolah dengan melibatkan siswa sebagai agen perubahan yang menciptakan suasana positif disekolah. penelitian ini bertujuan untuk mendeskripsikan (1) untuk mengetahui pelaksanaan Roots Day dalam membentuk akhlak kepada sesama, (2) Untuk mengetahui strategi dari program Roots Day dalam membentuk akhlak kepada sesama (3) Untuk mengetahui apa faktor penghambat dan pendukung dalam Program Roots Day dalam membentuk akhlak kepada sesama. Hasil penelitian menunjukan bahwasanya: (1) Program Roots Day dilaksanakan dengan penampilan teater mengenai bahaya perundungan dan deklarasi anti perundungan sebagai bentuk mewujudkan zona anti perundungan di sekolah, (2) Strategi dalam pelaksanaan program Roots Day dalam membentuk akhlak siswa dengan cara memberikan penjelasan mengenai bahaya perundungan, memberikan pendidikan akhlak, (3) Faktor pendukung diantaranya memberikan fasilitas dan anggaran dalam kegiatan Roots Day, antusias siswa dalam mengikuti kegiatan Roots Day dan antusian guru serta warga sekolah dalam pelaksanaan Roots Day. Untuk Faktor penghambat diantaranya, sebagian guru belum mendapatkan pelatihan khusus mengenai agen perubahan dalam program Roots Day, kebiasaan buruk di lingkungan rumah yang terbawa ke sekolah dan perbedaan karakteristik siswa.